Gestión financiera en el Gobierno Autónomo Descentralizado Parroquial Isla de Bejucal del cantón Baba, provincia de Los Ríos, en el periodo 2020. - Pacheco Miranda, Cinthia Yulissa (2022)
The present case study was carried out in the Bejucal Island Parish Autonomous Decentralized Government, it is a public sector entity that provides the necessary services to satisfy the needs of the citizens of the Bejucal Island sector, belonging to the Baba Canton, of the Province of Bejucal. Los Ríos, aims to determine financial management, which measures budget execution in the 2020 and 2021 periods, through bar graphs. In the development, the problems that this GAD has are described, for example, such as the scarcity budgeted directly from the institution, this case study has as research sublines companies and public and private institutions and the descriptive method is used since we allows you to observe the information and describe the problems. The importance of this work lies in verifying the execution of the Expenditure budget both in the year 2020 and in 2021 of the Parish GAD, in order to observe the variations that existed in these two years.